Comparison of perfusion 18F-FP-CIT PET and 99mTc-ECD SPECT in parkinsonian disorders. Issue 34 (27th August 2021) - Chun, KyungAh; Kong, EunJung; Cho, IhnHo
Abstract : Abstract: Early and accurate identification of various conditions that can cause parkinsonian symptoms is important for determining treatment policies. Currently dopamine transporter (DAT) imaging using FP-CIT, glucose metabolism imaging using fluorodeoxyglucose, cerebral blood flow image using ethyl cysteinate dimer (ECD), and others are used for differentiation. However, the use of multiple modalities is inconvenient and costly. In the present retrospective study, we evaluated the correlation between regional brain uptake ratios (URs) in perfusion FP-CIT PET and ECD SPECT images. Twenty patients with Parkinson's symptoms underwent perfusion DAT positron emission tomography ( 18 F-FP-CIT PET/CT) and cerebral blood flow tomography ( 99m Tc-ECD SPECT) within a 2-week period. Perfusion 18 F-FP-CIT PET/CT and 99m Tc-ECD SPECT URs of 19 brain regions (bilateral frontal, temporal, parietal and occipital lobes, bilateral caudate nucleus, bilateral putamen, bilateral insula, bilateral cingulate gyrus, bilateral thalamus, and brainstem) were directly compared and correlations were analyzed. Average 18 F-FP-CIT PET/CT regional perfusion URs were higher than 99m Tc-ECD SPECT URs. Uptake ratios were well correlated in all 19 regions (except right putamen), and especially in dopamine poor regions (cerebral cortex). In left putamen, URs were significantly correlated, but the correlation coefficient was lower than those of other regions. A single tracer dual phase N -3-fluoropropyl-2-beta-carboxymethoxy-3-beta-(4-iodophenyl) nortropane test seems to be helpful for differential diagnosis of parkinsonian disorders. Large-scale, longitudinal studies on complementary diseases with parkinsonian patterns are required to investigate differences in correlations between perfusion 18 F-FP-CIT PET/CT and 99m Tc-ECD SPECT over time.